1998
DOI: 10.1172/jci603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a high-fat diet on food intake and hypothalamic neuropeptide gene expression in streptozotocin diabetes.

Abstract: Insulin-deficient diabetic rats are markedly hyperphagic when fed a high-carbohydrate (HC) diet, but normophagic when fed a high-fat (HF) diet. When maintained on a HC diet, diabetic rats also exhibit increased gene expression of the orexigenic peptide neuropeptide Y (NPY) in the hypothalamic arcuate nucleus, and reduced expression of the anorectic peptide corticotropin-releasing hormone (CRH) in the paraventricular nucleus, and these changes are hypothesized to contribute to diabetic hyperphagia. In this expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 49 publications
6
39
5
Order By: Relevance
“…In contrast to AgRP, we found that NPY, POMC and CRH were not affected by 35 days of HF diet in the present study. These results are inconsistent with studies in mammals which showed that NPY, POMC and CRH levels were affected by a HF diet (Guan et al, 1998;Chavez et al, 1998;Lin et al, 2000;Lukaszewski et al, 2013), implying a genetic bluntness in the response to dietary fat in avian species.…”
Section: Involvement Of Agrp In the Hf-induced Decrease In Food Intakecontrasting
confidence: 58%
“…In contrast to AgRP, we found that NPY, POMC and CRH were not affected by 35 days of HF diet in the present study. These results are inconsistent with studies in mammals which showed that NPY, POMC and CRH levels were affected by a HF diet (Guan et al, 1998;Chavez et al, 1998;Lin et al, 2000;Lukaszewski et al, 2013), implying a genetic bluntness in the response to dietary fat in avian species.…”
Section: Involvement Of Agrp In the Hf-induced Decrease In Food Intakecontrasting
confidence: 58%
“…This difference could be due to a higher intake of energy from the high-carbohydrate diet than that from the high-fat diet. Such an effect has been documented in other studies in diabetic rats (19). The present effect of a high-fat diet on blood glucose is, however, different from that obtained in diabetes models with a positive energy balance and obesity, such as the diabetic Zucker fa/fa rat (7,9).…”
Section: Discussioncontrasting
confidence: 46%
“…Although there are plenty of calories in circulation, glucose is not available for oxidation. If diabetic rats are fed diets rich in fatty acids, an oxidizable fuel for diabetics, their hyperphagia subsides (32,72,76), estrous behavior is increased (4), and some measure of fertility may be restored (133).…”
Section: Calories Must Be Available For Oxidationmentioning
confidence: 99%